SEKOLAH KHUSUS / SLB MELATI CERIA SAMPIT - Manaku, Adi Wiratama; Andini, Dila Nadya (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
ABSTRACT According to the World Health Organization (WHO), around 5% of the world's population - about 466 million people - is diagnosed with what they call 'crippling hearing loss'. Although these statistics are divided into several levels of the inability of hearing, partial or total (hearing loss or the deaf), the percentage of the whole is characterized by hearing loss more than 40dB for adults and more than 30dB for children. The reduction of the capacity hearing does require a certain way to experience the environment. With the approach design principles "DeafSpace", which is based on the knowledge of the built environment, largely constructed for the people who bothered pendengaranya, presenting a variety of challenges addressed by the Deaf in a certain way to change their environment to fit with its environment.